MYCN-mediated transcriptional repression in neuroblastoma: the other side of the coin - Gherardi, Samuele; Valli, Emanuele; Erriquez, Daniela; Perini, Giovanni (Frontiers in Oncology, 2013)
Neuroblastoma is the most common extra cranial solid tumor in childhood and the most frequently diagnosed neoplasm during the infancy. MYCN amplification and overexpression occur in about 25% of total neuroblastoma cases and this percentage increases at 30% in advanced stage neuroblastoma. So far, MYCN expression profile is still one of the most robust and significant prognostic markers for neuroblastoma outcome. MYCN is a transcription factor that belongs to the family of MYC oncoproteins, comprising c-MYC and MYCL genes. Deregulation of MYC oncoprotein expression is a crucial event involved in the occurrence of different types of malignant tumors. MYCN, as well as c-MYC, can heterodimerize with its partner MAX and activate the transcription of several target genes containing E-Box sites in their promoter regions. However, recent several lines of evidence have revealed that MYCN can repress at least as many genes as it activates, thus proposing a novel function of this protein in neuroblastoma biology. Whereas the mechanism by which MYCN can act as a transcriptional activator is relatively well known, very few studies has been done in the attempt to explain how MYCN can exert its transcription repression function. Here, we will review current knowledge about the mechanism of MYCN mediated transcriptional repression and will emphasize its role as a repressor in the recruitment of a precise set of proteins to form complexes capable of down-regulating specific subsets of genes whose function is actively involved in apoptosis, cell differentiation, chemosensitivity and cell motility. The finding that MYCN can also act as a repressor has widen our view on its role in oncogenesis and has posed the bases to search for novel therapeutic drugs that can specifically target its transcriptional repression function.